LEGAL PROBLEMS AND PROSPECTS OF EVALUATING EVIDENCE IN ADMINISTRATIVE COURT PROCEEDINGS - Ismoilov , Ozodbek; Avloqulov , Azimbek (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article provides a scientific-theoretical and practical analysis of the institution of evidence evaluation in administrative court proceedings of the Republic of Uzbekistan. It examines the procedures for collecting, verifying, and evaluating evidence in administrative courts, as well as the judge’s decision-making based on inner conviction. The study highlights the legal assessment of evidence according to criteria such as relevance, reliability, and sufficiency.Furthermore, the article analyzes the role of written and electronic evidence in resolving administrative disputes, the active role of the court, and the challenges encountered in practice. Based on a comparative analysis with the experience of foreign countries, scientifically grounded proposals are developed to improve the system of evidence evaluation in administrative proceedings.